Measurement arrangement for the estimation of path loss exponent in wireless sensor network - Pu, Chuan Chin *; Lim, Soo Yong *; Ooi, Pei Cheng (2012)
Path loss model is generally used to relate distance and signal strength in wireless applications. This has been widely implemented in ranging, localization, and location tracking systems. A range of extension models have been proposed to enhance the performance for various environments and applications. Nevertheless, path loss exponent remains its significance as the main factor in the model regardless of how the model is varied. Based on the nature as an exponent of the model, inaccurate path loss exponent amplifies the error if it is used to estimate distance from received signal strength. Therefore, measurement of accurate value for path loss exponent becomes very important as it directly influences the output of distance estimation. Researchers have been studying the methods of measuring accurate path loss exponent in various environments. Instead of emphasizing the calculation process, this paper focuses more on the allocation of transmitters and receivers, and the arrangement among them. From the results obtained from experiments, properly arranged transmitter and receiver nodes provides better estimation of the path loss exponent. Based on the results, this paper also proposes a suitable nodes arrangement scheme for path loss exponent estimation.